Pengaruh Kecukupan Modal, Penyaluran Kredit dan Likuiditas Terhadap Profitabilitas Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2012 – 2021 - Hottua Samosir (Islamic Education Journal, 2026)
The research aims to test the effect of capital adequacy measured by Capital Adequacy Ratio (CAR), Credit Distribution measured by Loan to Deposit Ratio (LDR) and Liquidity measured by Current Ratio (CR), and Profitability measured by Return on Asset (ROA) of banking companies listed in the Indonesia Stock Exchange in 2012-2021 period. The study used a quantitative approach and the nature of research is explanatory. Data collection was performed by documentation and samples were drawn by purposive sampling where the samples were 26 companies out of 39 banking companies to be the populations. Data were proceded and analyzed with multiple linear regression analysis. Partially, variable of Capital Adequacy Ratio (X1) has a positive and significant effect on profitability (Y), the variable of Loan Distribution (X2) does not affect the profitability (Y), Liquidity (X3) does not affect the profitability (Y), and simultaneously variables of capital adequacy (X1), variable of Loan Distribution (X2) and variable of Liquidity (X3) have a positive and significant effect on profitability (Y). In Conclusion, partially variable of Capital Adequacy Ratio (X1) has a positive and significant effect on profitability (Y), the variable of Loan Distribution does not affect the profitability (Y), Liquidity (X3) does not affect the profitability, and simultaneously variables of capital adequacy, variable of Loan Distribution and variable of Liquidity have a positive and significant effect on profitability.